Accounting for changes in income inequality: Decomposition analyses for Great Britain, 1968 - 2009 - Mike Brewer; Liam Wren-Lewis (University of Essex, Institute for Social and Economic Research (ISER), 2012)
We analyse income inequality in Great Britain over the period 1968-2009 in order to understand why income inequality rose very rapidly over the period 1978-91 and then stopped rising. We find that earnings inequality has risen fairly steadily since 1978, but other factors that caused inequality to rise in 1978-91 have since reversed. Inequality in investment and pension income has fallen since 1991, as has inequality between those with and without employment. Furthermore, certain household types - notably the elderly and those with young children - which had relatively low incomes in 1978-91 have seen their incomes converge with others.
Keywords: 330